First time identification of subconjunctival Dirofilaria immitis in Turkey: giant episcleral granuloma mimicking scleritis - Aykur, Mehmet; Yagci, Ayse; Simsek, Sami; Palamar, Melis; Yaman, Banu; Korkmaz, Metin; Dagci, Hande (Springer, 2021)
Dirofilariasis is a vector-borne disease that is present worldwide. This report describes a giant subconjunctival granuloma which mimics scleritis, caused by D. immitis. A 60-year-old man was referred with the complaints of irritation, redness, and swelling at the medial part of the right eye. He was living in Izmir province located in western Turkey. Slit-lamp examination showed a firm, immobile mass measuring 13.0 x 5.0 x 5.0 mm with yellowish creamy color. The mass was completely removed surgically under local anesthesia mainly for diagnosis. Histopathology revealed typical morphological features of a filarioid nematode in favor of Dirofilaria as characterized by the external smooth cuticular surface, cuticular layer, muscle layer, and intestinal tubule. Molecular study was performed using DNA isolated from paraffin-embedded tissue sections of the worm. PCR amplification and then DNA sequence analysis of cytochrome c oxidase subunit 1 (cox1) gene fragment confirmed that the worm was D. immitis. It is suggested that this may represent the first human case of D. immitis occurring in subconjunctival granuloma in Turkey. Although rare, D. immitis caused by ocular dirofilariasis in humans should be considered.
Keywords: Dirofilaria immitis; Subconjunctiva; Human; Mitochondrial DNA analysis; Turkey